How the new substitute option influenced the Chinese Soccer Super League - Pan, P.; Song, H.; Huang, M.; Liu, T.; Memmert, D. (International Journal of Performance Analysis in Sport, 2025)
The purpose of this study was to analyse the influence of the new substitution option (NSO) on the Chinese Soccer Super League (CSL). After exclusion of matches included red cards, a total of 1129 match observations from 2018 to 2020 were analysed. Linear mixed models were built to analyse the impact of NSO on physical and technical performance. The study found that after the introduction of NSO: (i) substitution distributions changed, as substitution were made earlier by coaches than the past especially in the period from 46 to 75 min; (ii) although there was no significant changes on physical performance, technical performance showed significant changes especially in organizing performance and defending performance; (iii) specifically, teams used NSO showed significantly higher possession (p = 0.022), passes (p < 0.001), pass accuracy (p < 0.001), passes in attacking third (p = 0.004), and pass accuracy in attacking third (p < 0.001), whereas lower breakthroughs (p = 0.028), tackles (p = 0.002), clearances (p < 0.001), and yellow cards (p = 0.002). The findings of the study can help coaches, especially in CSL, to better understand NSO and improve decision-making when replacing players.